2020
DOI: 10.1055/a-1248-2626
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Bufadienolides from Toad Venom Identifies Gammabufotalin as a Potential Anti-inflammatory Agent

Abstract: Toad venom (Chansu) is used in the treatment of infectious and inflammatory diseases in China and East/Southeast Asian countries. However, the anti-inflammatory components of toad venom have not yet been systematically evaluated and clearly defined. To investigate the anti-inflammatory effects of toad venom and identify new anti-inflammatory ingredients, we used zebrafish, an alternative drug screening model, to evaluate the anti-inflammatory effects of 14 bufadienolides previously isolated from toad venom. Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 38 publications
(56 reference statements)
0
7
0
Order By: Relevance
“…Toad venom is the least frequently used animal venom in KM institutions (0.27%). While toad venom has toxic effects and causes gastrointestinal, mental, cardiac conduction, and arrhythmic disturbances [ 80 ], non-clinical studies have reported anti-inflammatory [ 81 ], antiplasmodial activity [ 82 ], and antiproliferative effects on cancer cells [ 83 ]. The treatment toxicity is the most important factor limiting its use [ 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…Toad venom is the least frequently used animal venom in KM institutions (0.27%). While toad venom has toxic effects and causes gastrointestinal, mental, cardiac conduction, and arrhythmic disturbances [ 80 ], non-clinical studies have reported anti-inflammatory [ 81 ], antiplasmodial activity [ 82 ], and antiproliferative effects on cancer cells [ 83 ]. The treatment toxicity is the most important factor limiting its use [ 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…Asthma is a chronic inflammatory disease, and Th2 cells, such as IL-4, IL-5 and IL-13, play key roles in asthma pathobiology [ 43 ]. The present study showed that the NF-κB signaling pathway plays a vital role during the process of inflammation [ 44 ]. According to Zhakeer et al [ 45 ], a mouse asthma model was developed by ovalbumin (OVA) sensitization and challenge in the BALB/c mice.…”
Section: Pharmacological Activities Of Bufadienolidesmentioning
confidence: 99%
“…Chemically, alkaloids ( Dai et al, 2018a ) and bufadienolides ( Qu et al, 2012 ) are the two main components in toad venom that exert their pharmacological effects ( Yang et al, 2015 ). Studies have confirmed that both alkaloids and bufadienolides majorly work to treat cancers ( Zhang et al, 2013 ; Yu et al, 2014 ; Meng et al, 2016 ; Chen et al, 2020a ; Dong et al, 2022a ), while bufadienolides also exert therapeutic effects in cardiovascular diseases and inflammation ( Zheng et al, 2022 ). Bufalin ( Figure 2 ), 3β,14-dihydroxy-5β-bufa-20,22-dienolide ( Zhang et al, 2020 ), has a molecular weight 386.53.…”
Section: Introductionmentioning
confidence: 99%
“…Toad venom (Chan-Su) is a traditional Chinese medicine (TCM) that has shown therapeutic efficacies for treating cancer, cardiovascular diseases, inflammation, etc. ( Li et al, 2021 ; Zheng et al, 2022 ). Chemically, alkaloids ( Dai et al, 2018a ) and bufadienolides ( Qu et al, 2012 ) are the two main components in toad venom that exert their pharmacological effects ( Yang et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%